Adverse Cutaneous Reactions Following COVID-19 Vaccination Among Patients with Pre-Existing Urticaria: A Cross-Sectional Study at a Tertiary Care Center in Saudi Arabia - Asiri A; Alotaibi HM; Alotaibi NA; Alsaleem AA (International Journal of General Medicine, 2025)
Ashwag Asiri,1 Hend M Alotaibi,2 Nouf Ali Alotaibi,3 Alfahdah Abdullah Alsaleem4 1Department of Child Health, College of Medicine, King Khalid University, Abha, Saudi Arabia; 2Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Department of Family Medicine, King Fahad Medical City, Riyadh, Saudi Arabia; 4Department of Pediatrics, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi ArabiaCorrespondence: Ashwag Asiri, Department of Child Health, College of Medicine, King Khalid University, P.O. Box 62527, Abha, Saudi Arabia, Email asalasiri@kku.edu.saPurpose: To investigate the incidence, characteristics, and associated factors of cutaneous adverse reactions to COVID-19 vaccines among adult patients with pre-existing urticaria in Saudi Arabia.Patients and Methods: A cross-sectional study enrolled 190 adult patients (≥ 18 years) with urticaria attending allergy/dermatology clinics at King Khalid University Hospital, Riyadh (November 2021–April 2022). Data on demographics, urticaria characteristics, vaccination status, cutaneous reactions, and comorbidities were collected via questionnaire. Statistical analyses included descriptive statistics, Chi-square/Fisher exact tests, Cochran’s test, and binary logistic regression.Results: Participants were predominantly female (87.4%), with chronic spontaneous urticaria (97.9%); 78.9% used regular antihistamines. Reactions occurred after dose 1 (22.7%), dose 2 (26.2%), and dose 3 (31.0%). Among symptomatic individuals, onset was typically < 24h, resolving in 1– 3 days for ~50%. Common reactions included injection site reactions (13.1– 16.3%), pruritus (7.8– 10.5%), and urticaria exacerbation (3.9– 9.1%). Urticaria exacerbation decreased significantly after dose 3 (p=0.030). Regular antihistamine use was associated with fewer reactions after dose 1 (adjusted OR 0.4, p=0.028). Female gender, asthma/atopy, and autoimmune disease were associated with specific reactions. Adjusted vaccine type showed no significant association.Conclusion: Cutaneous reactions post-COVID-19 vaccination in urticaria patients are relatively common but generally mild and transient. Decreasing urticaria exacerbations after dose 3 is reassuring. Regular antihistamine use may offer some protection, particularly after the first dose. Findings support vaccine safety and aid patient counseling.Plain Language Summary: Understanding how COVID-19 vaccines affect people with existing skin allergies is 41 crucial for public health. Our study focused on patients with urticaria (chronic hives) 42 who received COVID-19 vaccines. We found that while many patients experienced 43 mild skin reactions after vaccination, these reactions were generally temporary and 44 manageable. Most reactions occurred within 24 hours of vaccination and resolved within 45 a few days. Importantly, patients who regularly took antihistamine medications were 46 less likely to develop reactions. This research provides reassurance that COVID-19 47 vaccines can be safely administered to people with pre-existing urticaria, although some 48 may experience temporary symptoms. These findings help both healthcare providers 49 and patients make informed decisions about vaccination.Keywords: COVID-19, vaccine, urticaria, cutaneous adverse reaction, antihistamine, Saudi Arabia, cross-sectional study